C94. From Bay to Breaking Intensive Care Unit Capacity: Staffing, Strains and Stemming the Tide 2012
DOI: 10.1164/ajrccm-conference.2012.185.1_meetingabstracts.a6863
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between ICU Bed Availability, ICU Readmission And Cardiac Arrest On The General Wards

Abstract: Objective-The decision to admit a patient to the intensive care unit (ICU) is complex, reflecting patient factors and available resources. Previous work has shown that ICU census does not impact mortality of patients admitted to the ICU. However, the effect of ICU bed availability on patients outside the ICU is unknown. We sought to determine the association between ICU bed availability, ICU readmissions, and ward cardiac arrests.Design-In this observational study using data collected between 2009 and 2011, ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…outcome of the case. 8,9 Regardless of extensive resource consumption, the ICU costs are only acceptable if the quality of life saved is high and if the absolute risk reduction (ARR) is more than 5%. 10,11 Knowing the cost of the ICU will allow health planners and health service managers to utilize resources better.…”
Section: Introductionmentioning
confidence: 99%
“…outcome of the case. 8,9 Regardless of extensive resource consumption, the ICU costs are only acceptable if the quality of life saved is high and if the absolute risk reduction (ARR) is more than 5%. 10,11 Knowing the cost of the ICU will allow health planners and health service managers to utilize resources better.…”
Section: Introductionmentioning
confidence: 99%
“…However, the relationship between strain for non-COVID-19 patients was not explored (8). More generally in the nonpandemic literature, despite variation in how ICU capacity strain is measured, studies using the most commonly described indicators of strain consistently report an association with adverse outcomes, deviations in care processes, and changes in resource use (22)(23)(24)(25)(26)(27)(28). Furthermore, in a large retrospective cohort of 558 U.S. hospitals large surges in COVID-19 case load were found to significantly impact patient survival, eroding potential benefits of emerging therapies (29).…”
Section: Discussionmentioning
confidence: 99%
“…Town et al . [1] reported that the lack of ICU beds increases the rate of cardiac arrest and ICU readmission of patients discharged from an ICU to a general ward. This is because ICU patients are often transferred to a general ward without having undergone a sufficient recovery period [2].…”
Section: Introductionmentioning
confidence: 99%